2014
DOI: 10.1007/s11999-014-3784-6
|View full text |Cite
|
Sign up to set email alerts
|

Small Improvements in Mechanical Axis Alignment Achieved With MRI versus CT-based Patient-specific Instruments in TKA: A Randomized Clinical Trial

Abstract: Background Patient-specific instrumentation in TKA has the proposed benefits of improving coronal and sagittal alignment and rotation of the components. In contrast, the literature is inconsistent if the use of patient-specific instrumentation improves alignment in comparison to conventional instrumentation. Depending on the manufacturer, patient-specific instrumentation is based on either MRI or CT scans. However, it is unknown whether one patient-specific instrumentation approach is more accurate than the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
105
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(107 citation statements)
references
References 47 publications
(77 reference statements)
1
105
0
1
Order By: Relevance
“…For example, in the present study, the entire femoral preparation was completed first in order to optimize placement of the tibial cutting guide. Further, some studies used postoperative imaging as the reference standard [34], while others used intra-operative assessments based on computer-assisted navigation instruments [21,32,42]. In the sagittal plane, the KA2 group achieved an average slope closer to 3°of posterior slope (2.7°) compared to the VISIONAIRE group (4.4°).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the present study, the entire femoral preparation was completed first in order to optimize placement of the tibial cutting guide. Further, some studies used postoperative imaging as the reference standard [34], while others used intra-operative assessments based on computer-assisted navigation instruments [21,32,42]. In the sagittal plane, the KA2 group achieved an average slope closer to 3°of posterior slope (2.7°) compared to the VISIONAIRE group (4.4°).…”
Section: Discussionmentioning
confidence: 99%
“…However, Pfitzner et al [24] , recently published results comparing conventional instrumentation with CT and MRI based PSG from 2 different manufacturers, and between both PSG groups. They found a significant difference regarding the outliers in HKA-axis between MRI based PSG (Visionaire; 7%) and conventional instruments (43%), but no significant difference between CT based PSG and conventional instruments, neither between both PSG systems [24] . This was contrary to what Victor et al [25] found.…”
Section: Discussionmentioning
confidence: 99%
“…Outliers of the FFC for the PSG are comparable or less than the conventional intramedular technique. Only 2 authors published significant differences in favour of the MRI based PSG [17,24] . This was in contrast to the FTC (Table 7).…”
Section: Discussionmentioning
confidence: 99%
“…As such, substantial healthcare resources have been devoted to the development and use of patient-specific instrumentation (PSI), computer navigation, robotics, and other tools that help achieve a neutrally aligned TKA in the coronal plane [1,2,14]. On the other hand, some investigators support a different approach: The concept of a kinematically aligned TKA [6,[8][9][10].…”
mentioning
confidence: 99%